Religious Education in Baden-Powell’s Writings - Paola Dal Toso (Religions)
Robert Baden-Powell is well known as the founder of Scouting, an educational movement that spread rapidly around the world after 1907. This article aims to analyse an aspect of his writings that has been little studied: the religious dimension. A deeply religious man, Baden-Powell recognised the presence of God not only in the Bible but also in nature. It is interesting that some of his convictions are now, almost a hundred years later, topical educational insights. Baden-Powell encourages all Scouts in the world to cultivate religious practice by saying: “There can be no atheist Scout”. He offers concrete insights that commit the scout educator to take on the innate religious need that many young people express in a personal search for faith motivation.